2010
DOI: 10.1590/s0103-50532010000300004
|View full text |Cite
|
Sign up to set email alerts
|

Selective sorbent enrichment of nickel ions from aqueous solutions using a hierarchically hybrid organic-inorganic polymer based on double imprinting concept

Abstract: Este estudo envolve a preparação de um polímero orgânico-inorgânico impresso com íon (IIP) para o enriquecimento seletivo de Ni 2+ em soluções aquosas com posterior determinação por GF AAS. A rede polimérica híbrida foi preparada a partir de uma mistura do monômero funcional, 2-aminoetil-3-aminobutilmetildimetoxissilano e tetraetoxissilano como agente de ligação cruzada,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…Nevertheless, the search for selective sorbents has been extensive. In recent years, molecularly imprinted polymers (MIPs) have found applications as sensors and catalysts, in fluorescence spectroscopy, chromatographic separation, and MEPS for sample cleanup . The main advantages of MIPs are their low cost, robustness, resistance to a wide range of pH, temperatures and solvents, high mechanical strength, and storage stability .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the search for selective sorbents has been extensive. In recent years, molecularly imprinted polymers (MIPs) have found applications as sensors and catalysts, in fluorescence spectroscopy, chromatographic separation, and MEPS for sample cleanup . The main advantages of MIPs are their low cost, robustness, resistance to a wide range of pH, temperatures and solvents, high mechanical strength, and storage stability .…”
Section: Introductionmentioning
confidence: 99%
“…40 Nacano et al found the maximum adsorption capacity of the prepared nickel-imprinted polymers using 2-aminoethyl-3-aminobutylmethyldimethoxysilane as functional monomer as 5.44 mg g −1 . 41 Lenoble demonstrated the removal amount of nickel ions as 12.0 mg g −1 with the nickelimprinted polymers prepared in the presence of vinylbenzyl iminodiacetic acid. 42 However, none of these methods demonstrated the high specificity and selectivity by slight physical changes, such as pH and temperature.…”
Section: The Effect Of Initial Concentrationmentioning
confidence: 99%
“…52,54 Assim sendo, quando polímeros impressos são preparados via processo sol-gel fazendo uso de precursores funcionais, tais como 3-mercaptopropiltrimetoxissilano ou 2-aminoetilamina-3-propiltrimetoxissilano e do agente reticulante TEOS, o polímero resultante pode ser definido como polímero orgânico-inorgânico impresso. Esta definição é aceita, tendo em vista que o grupo alcoóxido metálico do precursor funcional reage com o TEOS por meio de reações de condensação e policondensação, permitindo a formação da matriz polimérica.…”
Section: Polímeros Híbridos Orgânicos-inorgânicos Impressos Com íOnsunclassified